Exploring Symbolic Narratives in Virtual Spaces: Leveraging Curiosity-Driven Design and the Attention-Value Model for Educational VR Museum Experiences - hajahmadi, shirin; Ghasempouri, Seyedali; Marfia, Gustavo (Mimesis Journal, 2024)
The article proposes the conceptualization, development, and exploration of a virtual reality (VR) project centered on symbolic storytelling. Drawing inspiration from Italo Calvino's Invisible Cities, especially the city of Tamara, the article delves into realms of creating an immersive VR narrative experience. The experience merges interactive narrative and puzzle elements, encouraging users to explore Tamara’s story through symbolic objects. It incorporates curiosity-driven design and the attention value model to captivate, and maintain, users’ attention with interactive features to deepen their engagement through a symbolic narrative. This research is valuable for museum educators and educational technology researchers, demonstrating an innovative method for creating immersive, interactive virtual experiences that effectively convey symbolic stories and concepts.